Enhancing organic waste decomposition with addition of phosphorus and calcium through different sources - Frank Oshioname Unuofin; Msimelelo Siswana (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose This study assessed the constituent element in rock phosphate (RP) that is responsible for enhancing quick decomposition of cow dung–waste paper mixtures during vermicomposting. Method Feedstock weighing 5 kg was achieved by mixing 2.16 kg shredded waste paper together with 2.84 kg cow dung sprinkled with water and then enriched with (1% P) as RP from triple superphosphate (TSP), phosphoric acid (PHA) and Ca in the form of CaCl2 at the level supplied by RP. After mixing, they were loaded into vermireactors and inoculated with matured earthworms at a stocking density of 12.5 g worms/kg feed for the entire 56 days. The decomposition of the mixtures was then monitored by measuring maturity parameters, a germination test for phyto-toxicity and morphological properties was assessed using scanning electron microscopy (SEM). Result Results revealed that rapid decomposition of waste was recorded where TSP was applied than RP whereas Ca-source had the least effect. A C:N ratio of 12 was achieved within 28 days where TSP was added, while RP, PHA and CaCl2 needed 42, 56 and more than 56 days, respectively. Conclusion It was evidently revealed from the results that P was basically the cause of the improved decomposition of the waste mixtures. To achieve quicker and well-humified enriched vermicompost with a C:N ratio of 10 within 20 days of vermicomposting, add water-soluble P sources.